Characterization of the microbunch time structure of proton pencil beams at a clinical treatment facility. (4th March 2016) - Petzoldt, J; Roemer, K E; Enghardt, W; Fiedler, F; Golnik, C; Hueso-González, F; Helmbrecht, S; Kormoll, T; Rohling, H; Smeets, J; Werner, T; Pausch, G
Abstract: Proton therapy is an advantageous treatment modality compared to conventional radiotherapy. In contrast to photons, charged particles have a finite range and can thus spare organs at risk. Additionally, the increased ionization density in the so-called Bragg peak close to the particle range can be utilized for maximum dose deposition in the tumour volume. Unfortunately, the accuracy of the therapy can be affected by range uncertainties, which have to be covered by additional safety margins around the treatment volume. A real-time range and dose verification is therefore highly desired and would be key to exploit the major advantages of proton therapy. Prompt gamma rays, produced in nuclear reactions between projectile and target nuclei, can be used to measure the proton's range. The prompt gamma-ray timing (PGT) method aims at obtaining this information by determining the gamma-ray emission time along the proton path using a conventional time-of-flight detector setup. First tests at a clinical accelerator have shown the feasibility to observe range shifts of about 5 mm at clinically relevant doses. However, PGT spectra are smeared out by the bunch time spread. Additionally, accelerator related proton bunch drifts against the radio frequency have been detected, preventing a potential range verification. At OncoRay, first experiments using a proton bunch monitor (PBM) at a clinical pencil beam have been conducted. Elastic proton scattering at a hydrogen-containing foil could be utilized to create a coincident proton-proton signal in two identical PBMs. The selection of coincident events helped to suppress uncorrelated background. The PBM setup was used as time reference for a PGT detector to correct for potential bunch drifts. Furthermore, the corrected PGT data were used to image an inhomogeneous phantom. In a further systematic measurement campaign, the bunch time spread and the proton transmission rate were measured for several beam energies between 69 and 225 MeV as well as for variable momentum limiting slit openings. We conclude that the usage of a PBM increases the robustness of the PGT method in clinical conditions and that the obtained data will help to create reliable range verification procedures in clinical routine.